2022
DOI: 10.3390/ijerph192214669
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Responders to Balneotherapy among Adults over 60 Years of Age with Chronic Low Back Pain: A Pilot Study with Trajectory Model Analysis

Abstract: Balneotherapy may be a relevant treatment for chronic low back pain (LBP) in individuals > 60 years old. This pilot study aimed to determine the effectiveness of balneotherapy for chronic LBP in people > 60 years old and to determine profiles of responders with trajectory model analysis. This was a pilot prospective open cohort study, with repeated measurements using validated questionnaires; participants were their own controls. The primary endpoint was the proportion of participants with a change in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
2
0
1
Order By: Relevance
“…It was observed that evaluation of the Visual Analogue Scale (VAS) at discharge recorded improvements, with significant relief of the pain. Protocols that combine specific rehabilitation treatments with balneotherapy, including hydrotherapy, mud baths and exercise in hot thermal mud, could reduce pain and disability in patients identified as responders [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that evaluation of the Visual Analogue Scale (VAS) at discharge recorded improvements, with significant relief of the pain. Protocols that combine specific rehabilitation treatments with balneotherapy, including hydrotherapy, mud baths and exercise in hot thermal mud, could reduce pain and disability in patients identified as responders [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The tests indicated for the diagnosis of sarcopenia can be performed for all cooperative, conscious patients who have multiple associated diseases. Likewise, rehabilitation treatments that use artificial and natural physical agents can be recommended to patients with kidney, liver or heart damage, without determining the side effects of drug treatments [ 7 , 8 , 9 , 10 , 13 , 20 , 21 ] The physical factors recommended in physical and rehabilitation medicine are considered environmentally friendly alternatives compared to drugs for the treatment of various pathologies [ 7 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pada intervensi balneotherapy yang diberikan pada usia 18 tahun keatas dengan keluhan low back pain mampu memberikan efek perbaikan dari rasa nyeri dengan menggunakan air yang memiliki suhu 60,2°C serta peningkatan kandungan SO4 2-sulfat dan mineral lainnya (Haji et al, 2021). Namun, berbeda hasilnya dengan penelitian yang dilakukan oleh Raud et al (2022), balneotherapy yang diberikan kepada pasien usia 60 tahun keatas dengan chronic low back pain tidak cukup mampu dalam mengurangi rasa nyeri jika tidak diiringi dengan edukasi dan/atau latihan yang disarankan untuk mendukung keberhasilan program intervensi. Sementara pada latihan berupa moderate hiking (ketinggian pendakian maksimal 1.500m dari permukaan laut) yang dikombinasi dengan intervensi balneotherapy Mg-Ca-SO4 terbukti mampu memberikan manfaat pada penurunan nyeri, meningkatkan mobilitas tulang belakang, mengurangi tingkat depresi, hingga meningkatkan kualitas hidup (Huber et al, 2019).…”
Section: Hasil Dan Pembahasanunclassified